A Methodological Approach to Use Technological Support on Teaching and Learning Data Structures - Messias Correia, Ronaldo Celso [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Olivete Junior, Celso [UNESP]; Brandi, Analice Costacurta [UNESP]; Cardim, Guilherme P. [UNESP]; IEEE (Ieee, 2014)
The Data Structure discipline consists on studying data organization in computer memory, primary and secondary ones. Data structures are organized using conceptual and behavioral issues that require high degree of abstract representation. It has been observed significant difficulty, by students, to understand the abstract concepts related, which is observed during practical tasks. In fact, practical tasks are essential to consolidate knowledge about data structures, but the students need support to understand the concepts before practical tasks. There are several works in literature showing tools to support conceptual and behavior comprehension, each one with specific features. However, the tools by themselves are not enough, dealing with specific data structure, with severe constraint. In literature, some tools are presented using case studies specific to the data structures supported. And we observed that the tools are presented focusing on their functionalities (the case studies are designed to explore such functionalities). Also, we observed the lack of a methodological approach to incorporate tools in a learning process effectively. In this scenario, we address the use of technological support to teaching-learning process. We propose a methodology based on constructionism, in which students, tasks (home works) and tools are coordinated by a teacher in favor of knowledge construction. In order to present our methodology, we use a learning tool, named CADILAG, developed using visual resources to support students understand data structures concepts. We applied the methodology proposed for two years. The positive results are observed in students grades and their evaluation. Also, according to the teacher, the students have shown interest and motivation.
Keywords: Data Structure; Learning Tool; Visualization; Cognitive Load; Education; Computing